There is value in treating elevated levels of diabetes distress: the clinical impact of targeted interventions in adults with Type 1 diabetes. Issue 1 (5th August 2019) - Hessler, D.; Fisher, L.; Polonsky, W.; Strycker, L.; Parra, J.; Bowyer, V.; Dedhia, M.; Masharani, U.
What's new?: Few interventions have been aimed directly at reducing diabetes distress among adults with Type 1 diabetes. Recently, the T1‐REDEEM study reported large reductions in diabetes distress following participation in either an education‐focused or affective‐focused intervention programme; however, the effect of these interventions compared with usual care is not documented. The present study documents statistically significant and clinically meaningful larger reductions in diabetes distress following intervention compared with non‐intervention in adults with Type 1 diabetes. The results add to the growing literature highlighting the critical need for the development and implementation of distress‐targeted interventions in the provision of comprehensive diabetes care. Abstract: Aim: To compare the effect of targeted interventions to reduce high diabetes distress among adults with Type 1 diabetes with a comparison sample of similar but untreated individuals, and to document the stability of untreated diabetes distress over time. Methods: A total of 51 adults with Type 1 diabetes with elevated baseline diabetes distress (distress score ≥ 2.0) and HbA1c levels (≥ 58 mmol/mol) were identified from a longitudinal, non‐intervention study, and compared with a similar sample of 51 participants in an intervention study. Both groups completed the T1‐DDS diabetes distress questionnaire at baseline and 9 months. Results: Large and significant reductions in diabetes distress scores were recorded in the intervention group (mean ± sd change = –0.6 ± 0.6), while minimal change was found in the non‐intervention group (–0.2 ± 0.6, group effect P = 0.002; effect size d = 0.67). Additional analyses using the established minimal clinically important difference for the T1‐DDS showed that diabetes distress increased significantly (minimal clinically important difference ≥ 1) or persisted at high levels for 51% of participants in the non‐intervention group, compared with 23.5% in the intervention group. Conclusion: Our results showed that targeted interventions led to dramatic reductions in diabetes distress compared with a lack of treatment. We also conclude that elevated diabetes distress, when left unaddressed, does not resolve over time and often remains chronic. (Clinical Trials Registry no.: NCT02175732)